Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.3109/0142159x.2013.802296
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining empathy in medical school: It is possible

Abstract: Background: Empathy is an indispensable skill in medicine and is an integral part of 'professionalism' . Yet, there is still increasing concern among medical educators and medical professionals regarding the decline in medical students' empathy during medical education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
63
4
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(83 citation statements)
references
References 47 publications
11
63
4
5
Order By: Relevance
“…Consistent with prior studies [57], men had a less positive attitude toward physician empathy in all of the multivariate models. However, the strength of this gender effect decreased (−.21 to −.09) when the individual disposition variables were entered into the model.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with prior studies [57], men had a less positive attitude toward physician empathy in all of the multivariate models. However, the strength of this gender effect decreased (−.21 to −.09) when the individual disposition variables were entered into the model.…”
Section: Discussionsupporting
confidence: 89%
“…70 Interestingly, other reports in Portuguese medical students have detected higher empathy scores in later curricular years, 71,72 showing that patient-care activities and continuous socioemotional stimulation can increase empathic ability. 69,[73][74][75] In our study, we unveiled significant associations between attachment styles and empathy.…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies have reported differences in the level of empathy by ethnicity and gender . Cultural differences do partly explain these variances in the level of empathy as emotional arousal, a characteristic of empathy is expressed differently across culture .…”
Section: Discussionmentioning
confidence: 92%
“…The lack of attention into the emotional component of empathy could be attributed to the inconsistencies in the level of empathy across different ethnicities and gender Ethnicities/culture can play a role in how emotions are felt and expressed in certain situation, hence understanding cultural differences is critical to appreciate emotions and to recognise the role of empathy. It has been suggested that cultural differences exist in emotional arousal level between the east and the west.…”
Section: Introductionmentioning
confidence: 99%